2010
DOI: 10.1074/jbc.m110.148981
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Is Required for Transfer of the Cholera Toxin A1 Subunit from the Endoplasmic Reticulum to the Cytosol

Abstract: Cholera toxin (CT) is an AB 5 toxin that moves from the cell surface to the endoplasmic reticulum (ER) by retrograde vesicular transport. In the ER, the catalytic A1 subunit dissociates from the rest of the toxin and enters the cytosol by exploiting the quality control system of ER-associated degradation (ERAD). The driving force for CTA1 dislocation into the cytosol is unknown. Here, we demonstrate that the cytosolic chaperone Hsp90 is required for CTA1 passage into the cytosol. Hsp90 bound to CTA1 in an ATP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(106 citation statements)
references
References 49 publications
5
100
0
1
Order By: Relevance
“…Moreover, HSP90 was recently shown to mediate dislocation of the cholera toxin A1 (CTA1) subunit from the ER into the cytosol. ER-to-cytosol export of CTA1 requires association of HSP90 with CTA1, a process blocked by GA treatment (39). Thus, the Hsp90-mediated translocation system might have developed as a common mechanism in a variety of cell types, ultimately leading to an assortment of seemingly unrelated effects such as transcriptional activation (36), intoxication (38), and cross-presentation (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HSP90 was recently shown to mediate dislocation of the cholera toxin A1 (CTA1) subunit from the ER into the cytosol. ER-to-cytosol export of CTA1 requires association of HSP90 with CTA1, a process blocked by GA treatment (39). Thus, the Hsp90-mediated translocation system might have developed as a common mechanism in a variety of cell types, ultimately leading to an assortment of seemingly unrelated effects such as transcriptional activation (36), intoxication (38), and cross-presentation (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic Hsp90 has been shown to participate in the posttranslational targeting of preproteins to the TOC-TIC and translocase of the outer membrane-translocase of the inner membrane (TOM-TIM) import machinery of chloroplasts and mitochondria, respectively (30,40). It was recently reported that cytosolic Hsp90 participates in translocation of antigen across the endosomal membrane into the cytosol in mammalian cells and also in dislocation of the cholera toxin A1 subunit from the ER into the cytosol (41,42). We provide unique evidence for the involvement of an organellar Hsp90 in protein translocation (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The medium was removed and replaced with serum-free medium containing various concentrations of CT. After 2 h, the cells were processed for determination of cAMP levels as described in Ref. 34. The basal levels of cAMP determined from unintoxicated cells were background-subtracted from the values obtained for toxin-treated cells; the maximal response from the parental control cells was arbitrarily set to 100%; and all other results were expressed as ratios of that 100% value.…”
Section: Labeling and Purification Of Cta1-hismentioning
confidence: 99%
“…For the toxicity assay, cells were exposed to ice-cold acidic ethanol at 3 h post-transfection and were processed for determination of cAMP levels as described in (34). An additional set of transfected cells were chased overnight to determine the relative levels of CTA1 expression via metabolic labeling and immunoprecipitation.…”
Section: Labeling and Purification Of Cta1-hismentioning
confidence: 99%
See 1 more Smart Citation